2016
DOI: 10.1088/1748-6041/11/3/035015
|View full text |Cite
|
Sign up to set email alerts
|

Towards antimicrobial yet bioactive Cu-alginate hydrogels

Abstract: The simplest approach to enhance alginate hydrogel characteristics and functional properties is to replace the calcium in the process of alginate gelation with other metallic ions which are essential for living systems. Gelling of alginate with other ions and using modern encapsulation techniques can provide new delivery systems with required properties. Hence, in this study Cu-alginate hydrogels in the form of microbeads were produced by electrostatic extrusion using gelling solutions with Cu(II) concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 59 publications
1
23
0
1
Order By: Relevance
“…On the other hand, Cu(II) itself released from the beads and diffusing in agar can act as an antimicrobial agent. Microbeads of copper-alginate hydrogels induced immediate bactericidal effects against Escherichia coli and Staphylococcus aureus (Malagurski et al 2016). The bead made without Cu(II) did not inhibit bacterial growth, indicating that the amount of oligomers released from the bead was innocuous, consistent with the results of cytotoxicity assays.…”
Section: Bacterial Inhibition Assaysupporting
confidence: 70%
“…On the other hand, Cu(II) itself released from the beads and diffusing in agar can act as an antimicrobial agent. Microbeads of copper-alginate hydrogels induced immediate bactericidal effects against Escherichia coli and Staphylococcus aureus (Malagurski et al 2016). The bead made without Cu(II) did not inhibit bacterial growth, indicating that the amount of oligomers released from the bead was innocuous, consistent with the results of cytotoxicity assays.…”
Section: Bacterial Inhibition Assaysupporting
confidence: 70%
“…Cu–SA hydrogels prepared through electrostatic extrusion were bactericidally effective against E. coli and MRSA ( Figure 5 ). 49 Cu–SA hydrogels, with higher Cu(II) loading (≈100 × 10 −6 m ), were produced by electrostatic extrusion using gelling solutions with Cu(II). The Cu–SA hydrogels exhibited immediate bactericidal effects against S. aureus and E. coli .…”
Section: Inorganic Antibacterial Agent‐incorporated Hydrogelsmentioning
confidence: 99%
“…ZEO/PVA hydrogel with 0.48 wt% and higher cobalt‐exchanged ZEO contents showed efficient antibacterial activities against G− bacteria (i.e., E. coli and S. aureus ). Cu–SA hydrogels prepared through electrostatic extrusion were bactericidally effective against E. coli and MRSA ( Figure ) . Cu–SA hydrogels, with higher Cu(II) loading (≈100 × 10 −6 m ), were produced by electrostatic extrusion using gelling solutions with Cu(II).…”
Section: Inorganic Antibacterial Agent‐incorporated Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Madzovska-Malagurski et al synthesized bioactive Cualginate hydrogels and showed their bactericidal activity against Escherichia coli and Staphylococcus aureus. 31 Nevertheless, the long-term toxic effects induced by leached metal ions (silver and copper) questions their utility for water treatment.…”
Section: Introductionmentioning
confidence: 99%